Pengaruh Total Asset Turnover (TATO) dan Earning Per Share (EPS) Terhadap Dividen Payout Ratio pada Perusahaan Sub Sektor Farmasi yang Terdaftar di BEI (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of Total Asset Turnover (TATO) and Earning Per Share (EPS) on the Dividend Payout Ratio (DPR) in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The study uses a quantitative approach with an associative method. The research sample consists of five companies selected using a purposive sampling technique. Data were obtained from the companies' financial statements and analyzed using multiple linear regression with the help of SPSS. The results show that partially Total Asset Turnover (TATO) has a significant effect on the Dividend Payout Ratio (DPR), indicating that the company's effectiveness in utilizing assets to generate sales contributes to the dividend distribution policy. Conversely, Earning Per Share (EPS) does not have a significant effect on DPR, so that the amount of earnings per share is not necessarily followed by an increase in the proportion of dividends distributed to shareholders. Simultaneously, TATO and EPS have a significant effect on DPR. However, the ability of both variables to explain variations in DPR is still relatively low, with an Adjusted R Square value of 17.2%, indicating that there are other factors that are more dominant in influencing the dividend policy of pharmaceutical companies. This finding indicates that asset utilization efficiency is a more important factor than earnings per share in determining the Dividend Payout Ratio.